Konflik Ekologis dan Representasi Lingkungan dalam Novel Kekal Karya Jalu Kancana: Perspektif Ekokritik Sastra Lawrence - Natasya Julianti; Emi Agustina; Yayah Chanafiah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to describe the ecological conflicts and environmental representations in the novel Kekal karya Jalu Kancana based on Lawrence Buell’s ecocritical literary theory. The study is motivated by the growing concern over environmental degradation, which is also represented in literary works as a form of criticism and reflection on the relationship between humans and nature. Through an ecocritical approach, this research seeks to reveal how ecological conflicts and environmental issues are portrayed in the novel. This study employed a descriptive qualitative method with an ecocritical literary approach. The data consisted of words, sentences, dialogues, and narratives containing ecological conflicts and environmental representations in the novel Kekal karya Jalu Kancana. The primary data source was the novel Kekal by Jalu Kancana, published in 2019. Data were collected through library research by reading, marking, and recording relevant data. The data were analyzed through the processes of identification, classification, description, and interpretation based on Lawrence Buell’s ecocritical literary theory. The findings reveal that the ecological conflicts in the novel include the exploitation of nature for human interests, conflicts of human interests with ecological impacts, unequal relationships between humans and nature based on anthropocentric perspectives, multilayered ecological impacts, and ecological conflicts as environmental criticism. Environmental representation is reflected through the environment as an essential part of life, a shared living space, a moral responsibility, and an entity that continuously changes human actions. This study demonstrates that the novel emphasizes the importance of ecological awareness and human responsibility in preserving environmental sustainability.